(untitled) (Journal of actual problems of jurisprudence, 2019)
This article analyzes the statistical material on human trafficking in the Republic of Kazakhstan, discussed the legal issues of human trafficking in Kazakhstan, and their criminalization, the degree of exploration of these issues in the legal literature